The relationship between sports activity and the menstrual cycle of adolescent girls S-1 Midwifery Hafshawaty Zainul Hasan University - Hartanto, Hartanto; Sary, Yessy Nur Endah (Universitas Tanjungpura, 2024)
Regular exercise for fitness is one of the best ways to reduce stress. Lack of sports activity can affect weak physical conditions and can cause stress, so this has an impact on mental health, emotional physiology in humans, especially women and the menstrual cycle in the reproductive system. The purpose of the study was to determine how much the relationship between sports activity and the menstrual cycle. This type of research is quantitative research. The sampling technique in this study used total sampling. The total sample was 37 midwifery S-1 students of Hafshawaty Zainul Hasan University Genggong level one 2024. The instruments used in this study are: (1) observation guideline sheet, questionnaire questionnaire. Data analysis techniques used in this study include: correlation coefficient test (r), hypothesis testing (test) t. The results of research on the relationship between sports activity and the menstrual cycle of adolescent girls obtained Person correlation data of 0.366; 0.03 0.05. It can be concluded that the data from the Sports Activity scale with the Menstrual Cycle is normally distributed and a significant direct relationship and sports activity is one of the factors that influence the menstrual cycle. The conclusion in this study is that there is a significant relationship between sports activity and the menstrual cycle of adolescent girls S1 midwifery Hafshawaty Zainul Hasan University Genggong Probolingo.